The Relationship Between Low-Density Lipoprotein Cholesterol and Progression of Mild Cognitive Impairment: The Influence of rs6859 in PVRL2 - Xiao, Qianyi; Xi, Jianxiong; Wang, Ruru; Zhao, Qianhua; Liang, Xiaoniu; Wu, Wanqing; Zheng, Li; Guo, Qihao; Hong, Zhen; Fu, Hua; Ding, Ding (Frontiers in Genetics, 2022)
Background: Genome-wide association studies have identified many Alzheimer's Disease (AD) genetic-risk single nucleotide polymorphism (SNP) and indicated the important role of cholesterol/lipid metabolism pathway in AD pathogenesis. This study aims to investigate the effects of cholesterol and genetic risk factors on progression of mild cognitive impairment (MCI) to AD. Methods: We prospectively followed 316 MCI participants aged  50 years with a baseline cholesterol profile and SNP genotyping data for 4.5 years on average in a sub-cohort of the Shanghai Aging Study. Total cholesterol, low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol in serum were measured at baseline. SNP genotyping was performed using a MassARRAY system. At follow-up, consensus diagnosis of incident dementia and AD were established based on medical, neurological, and neuropsychological examinations. Cox regression models was used to assess the association of cholesterol and SNP with incident AD. Results: The AG/AA genotypes of PVRL2 rs6859 was significantly associated with increased incident AD in MCI participants, compared with GG genotype (adjusted hazard ratio [HR] 2.75, 95% confidence interval [CI] 1.32–5.76, P = 0.007, false discovery rate–adjusted P = 0.030). In PVRL2 rs6859 AG/AA carriers, each-1 mmol/L higher level of LDL-C was significantly associated with a 48% decreased risk of AD (adjusted HR 0.52, 95%CI 0.33–0.84, P = 0.007). Consistent results were obtained when using LDL-C as the categorical variable (P for trend = 0.016). Conclusion: the relationship between LDL-C and progression of MCI may be influenced by genetic variants.